Topical and Systemic Formulation Options for Cutaneous T Cell Lymphomas - Taku Fujimura; Ryo Amagai; Yumi Kambayashi; Setsuya Aiba (MDPI AG, 2021)
Although various anti-cutaneous T-cell lymphoma (CTCL) therapies are available for clinical use, appropriate chemotherapy lines for the treatment of CTCLs have yet to be established. Therefore, to date, various clinical trials for the treatment of advanced CTCLs are ongoing. In this review, we evaluate the therapeutic options that are available in clinical practice for treatment of early- and advanced-stage CTCLs (targeted therapies, histone deacetylase (HDAC) inhibitors, retinoids, interferons, cytotoxic drugs, etc.). We also examine clinical trials of novel regimens for the treatment of CTCLs.